2013
DOI: 10.1371/journal.pone.0069943
|View full text |Cite
|
Sign up to set email alerts
|

Mating Increases Neuronal Tyrosine Hydroxylase Expression and Selectively Gates Transmission of Male Chemosensory Information in Female Mice

Abstract: Exposure to chemosensory signals from unfamiliar males can terminate pregnancy in recently mated female mice. The number of tyrosine hydroxylase-positive neurons in the main olfactory bulb has been found to increase following mating and has been implicated in preventing male-induced pregnancy block during the post-implantation period. In contrast, pre-implantation pregnancy block is mediated by the vomeronasal system, and is thought to be prevented by selective inhibition of the mate’s pregnancy blocking chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…To further explore this issue we examined the effects of two neuromodulators, carbachol and dopamine, known to be active in the AOB (Dong et al, 2009 ; Matthews et al, 2013 ) on the sustained firing responses and DAPs in AOB mitral cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further explore this issue we examined the effects of two neuromodulators, carbachol and dopamine, known to be active in the AOB (Dong et al, 2009 ; Matthews et al, 2013 ) on the sustained firing responses and DAPs in AOB mitral cells.…”
Section: Resultsmentioning
confidence: 99%
“…M1 activation was shown to enhance persistent firing in both granule and mitral cells of the AOB (Smith and Araneda, 2010 ). Other neuromodulators known to be active in the AOB are noradrenaline and dopamine (Dong et al, 2009 ; Matthews et al, 2013 ), both shown to be associated to the AOB-mediated mate recognition in mice (Brennan, 2009 ). Interestingly, both acetylcholine and dopamine were recently linked to the atypical social behavior of BTBR mice (Karvat and Kimchi, 2014 ; Squillace et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting at a concentration of 1–2 μg/mL detects a band of approximately 72 kDa. Immunoperoxidase and immunofluorescence detections of DβH were conducted in sections of mouse brains, and DβH was also expressed in cell cultures (Polanski et al ., ; Matthews et al ., ). The monoclonal antibody against HA‐α2A‐AR was generated in mouse against the 12‐amino‐acid peptide CYPYDVPDYASL.…”
Section: Discussionmentioning
confidence: 97%
“…The major sources of DA are the DA‐releasing neurones of the ventral midbrain, mainly originated in the VTA, ZI and substantia nigra pars compacta . Increased levels of TH expression are often used to indicate enhanced DA synthesis and release . Therefore, the TH‐IR neurones observed in the VTA and ZI were likely to have been dopaminergic.…”
Section: Discussionmentioning
confidence: 99%